2014
DOI: 10.4172/2161-1122.1000215
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case Of Introral Lipoma In A 33 Months Old Child And A Review

Abstract: The lipoma presents as one of the common mesenchymal neoplasms however, in the oral and maxillofacial region its occurrence is less frequent, representing about 0.5% to 5% of all benign oral tumours. Most patients with lipomas are above 40 years of age or older, lipomas are uncommon in children and with gender distribution appearing to be approximately equal. Lipomas are usually asymptomatic until they grow to large size and may interfere with speech and mastication. Other benign connective tissue lesions such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The first description of an oral lipoma was given by Roux in 1848 [5], which he referred to as "yellow epulis". Lipomas are benign soft tissue neoplasms of mature adipose tissue rarely seen in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The first description of an oral lipoma was given by Roux in 1848 [5], which he referred to as "yellow epulis". Lipomas are benign soft tissue neoplasms of mature adipose tissue rarely seen in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Lipomas are rare soft tissue tumours in children. Although it is the commonest mesenchymal neoplasms but its prevalence in maxillofacial region is less frequent [29]. Our study found 1 case in maxillofacial region which presented in second decade of life.…”
Section: Resultsmentioning
confidence: 45%
“…[ 4 ] Although oral lipomas are well-circumscribed soft tissue lesions, rarely they give a radiographic impression of an intraosseous neoplasm within the mandibular canal. [ 14 ] Lipomas may show radiographic features rarely manifesting as radiolucency. [ 10 ] The gross specimen of lipoma when placed in a pot with water usually floats in it.…”
Section: Discussionmentioning
confidence: 99%